POSTGRADUATE PERFORMANCE OF UNIVERSITAS NEGERI SURABAYA DURING THE COVID-19 PANDEMIC PERIOD - Sofianto, Mochamad Firmansyah (Universitas Nahdatul Ulama Surabaya, 2021)
Abstract: Since the Covid-19 Pandemic, all Government Institutions and Units must work at home or called Work From Home (WFH), including learning which is also carried out online. After running for 2 months or more, the implementation of the office and learning needs to be evaluated. So this study aims to describe the performance of leaders, lecturers, and teaching staff at the Unesa Postgraduate Program during the Covid-19 Pandemic. Data was obtained from March to October 2020, during the Covid-19 Pandemic. This study was designed as a population study, namely research using the entire population as a sample, namely all lecturers, education staff, and students. The data will be analyzed by quantitative descriptive analysis with narrative explanation. The results are (1) the performance of the leadership, namely the Director, Deputy Director for Academic and Student Affairs, and Deputy Director for General Affairs, is in good/high criteria although there are still some respondents' points below the average. (2) The performance of the Head of Study Programs is classified into 3 groups, namely groups with very high/very good, high/good, and moderate categories. The very high/very good group had 2 head of study programs, the high//good group had 16 head of study programs, and the medium group had 6 heads of study programs. (3) Lecturer performance is based on self-assessment, the biggest obstacle is signal/network problems, the second obstacle is difficulty in understanding the material and sequentially is limited quota, difficult to measure student participation/attitude, application, less able to use distance learning models, devices, health /tired/stress/indeterminate working hours, potential fraud, and administration. (6) The performance of education personnel based on the assessment of the head of the sub-section that still needs to be improved is the quantity of work according to the target, the ability to carry out tasks online well, and carrying out tasks at home must be equipped with personal facilities Meanwhile, based on student assessments, some things that still need to be improved are the ability to work together in completing assignments, the quantity of work done according to the target, the ability to carry out tasks online well, and carrying out tasks at home must be equipped with personal facilities. Keywords: Performance assessment, Director and Vice Director, Staff academic and Lecturer, Postgraduate Program, Pandemic of Covid-19 Abstrak: Sejak adanya Pandemic Covid-19, semua Lembaga dan Unit Pemerintah harus bekerja di rumah atau disebut Work From Home (WFH), termasuk pembelajaran juga dilaksanakan secara online sistem. Setelah berjalan selama 2 bulan atau lebih, pelaksanaan kantor dan pembelajaran perlu dilakukan evaluasi. Sehingga penelitian ini bertujuan untuk mendeskripsikan kinerja pimpinan, dosen, dan tenaga pendidik di Program Pascasarjana Unesa selama Pandemic Covid-19. Data diperloah dari mulai bulan Maret sampai Oktober tahun 2020, selama Pandemic Covid-19. Penelitian ini didesain sebagai penelitian populasi yaitu penelitian dengan menggunakan semua populasi sebagai sampel yaitu semua dosen, tenaga kependidikan, dan mahasiswa. Data akan dianalisis dengan analisis deskriptif kuantitatif dengan penjelasan secara narasi. Hasilnya adalah (1) kinerja pimpinan yaitu Direktur, Wakil Direktur Bidang Akademik dan Kemahasiswaan, dan Wakil Direktur Bidang Umum masuk kriteria baik/tinggi walaupun masih ada beberapa poin responden yang dibawah rata-rata. (2) Kinerja dari kaprodi digolongkan menjadi 3 kelompok, yaitu kelompok dengan kategori sangat tinggi/sangat baik, tinggi/baik, dan sedang. Kelompok sangat tinggi/sangat baik terdapat 2 kaprodi, kelompok tinggi//baik terdapat 16 kaprodi, dan kelompok sedang terdapat 6 kaprodi. (3) Kinerja dosen berdsarakan penilaian diri, hambatan terbesar adalah masalah sinyal/jaringan, hambatan kedua adalah kesulitan pemahaman materi dan secara berurutan adalah terbatasnya kuota, sulit mengukur partisipasi/sikap mahasiswa, aplikasi, kurang bisa menggunakan model pembelajaran jarak jauh, perangkat, kesehatan/lelah/stress/jam kerja tak tentu, potensi kecurangan, dan administrasi. (6) Kinerja tenaga kependidikan berdasarkan penilaian Kasubag yaitu masih perlu ditingkatkan adalah kuantitas hasil kerja sesuai target, kemampuan melaksanakan tugas secara online dengan baik, dan pelaksanaan tugas dirumah harus dilengkapi dengan fasilitas pribadi. Sedangkan berdasarkan penilaian mahasiswa beberapa yang masih harus ditingkatkan adalah kemamapuan kerja-sama dalam menyelesaikan tugas, kuantitas hasil kerja sesuai target, kemampuan melaksanakan tugas secara online dengan baik, dan pelaksanaan tugas dirumah harus dilengkapi dengan fasilitas pribadi. Kata kunci: Penilaian kinerja; Direktur dan wakil direktur; Tendik dan dosen; Pascasarjana; Pandemik Covid-19